A Construção passiva analítica na fala do Presidente Lula: uma estratégia de sombreamento - Camargo, Hyléa de (2011)
Construction Grammar is a theory of language that is concerned with the ature of language proficiency of the speaker, looking at the integration of language structures and cognitive processes, being, therefore, human-centered. In his version of Construction Grammar, Adele Goldberg (1995) postulates that basic sentences are constructions, to the extent that they correspond to form-meaning pairings that exist independently of verbs instantiated. It is in this context that this research aims to investigate the passive structure of the language whose form-meaning relation proposes to weaken the participants of enunciation scenes through a discursive strategy known as shading, in Goldberg's terms. In the political scene, there is a fertile environment for research of this phenomenon, due to the urgency of the speakers of these communicative events in not elaborating on the discursive participants, whenever this favors them politically. In the case of the political universe, the president is the most exposed to dialogues, so President Lula's interviews from July through December 2005, 2006 and 2010, respectively, during the "mensalão", His re-election and the election of Dilma Rousseff, available from the website of the government (www.info.planalto.gov.br) and classified in types,were used as the corpus of this research. The observation and analysis of the data fall on three remarkable periods in the presidential history of Luiz Inacio Lula da Silva, tense periods due to allegations of corruption and attempts to keep himself, as well as the Partido dos Trabalhadores (PT), in the control of the nation. As a result, it is a favorable period for constructions that lead to camouflage the agents, as observed during the development of this research, confirming the thesis that analytical passive constructions are a strategy of shading discursive agents.